Dampak Peran Pendamping Terhadap Pengembangan UMKM Di Kelurahan Kabonena Kota Palu Sulawesi Tengah - Astrid Widya Ningsih; Harnida Wahyudi Adda; Niluh Putu Evvy Rossanty; Faruq Lamusa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to identify and describe the impact and benefits of the role of companion on the development of MSMEs in Kabonena Village. The role of MSME assistants will be analyzed using the four roles and skills presented by Jim Ife and Frank Tesoreiro (2006), namely the facilitative role, educational role, representational role and technical role. The type of research that the author uses in this writing is qualitative research with data collection techniques, namely: observation, in-depth interviews and documentation studies related to the research problem. The results of the research found that through a facilitative role, MSME actors will have the enthusiasm to run a business, the group is facilitated through various ideas and concepts in running a business, and there is a personal approach for each group member when there are problems within the group. In an educational role, the mentor will increase the awareness of all group members regarding the importance of the business they are running and provide information that is important for the development of their business. The third, in the role of accompanying representation, will help the group in using the right media in developing their business, building working networks with other parties, and sharing knowledge and experience. And finally, the role and technical skills, the assistant helps the group to use computers, and make verbal and written presentations, in running and developing their business.